Description of Adolescent Women's Knowledge About Abortion and Reproductive Health In SMA Negeri Kendari, Poasia District, Kendari City - Fety, Yulli; Kiran, Princess (Green Publisher Indonesia, 2022)
Based on survey Preliminary done researcher at SMA Negeri 2 Kendari, interview conducted against 15 students there are 9 students not yet knowing about causes and dangers abortion. While 6 students already knowing about causes and dangers abortion. interview conducted about health reproduction of 15 girls there are 8 people who haven't knowing about personal hygiene tool reproduction and personality hygine at the moment menstruation. While 7 girls other already knowing about personal hygiene tool reproduction and personality hygine at the moment menstruation. Destination Research: for knowing description knowledge teenager Princess about abortion and health reproduction in SMA Negeri 2 Kendari. Method Research: using method Descriptive, population in study this totaling 474 students. Taking sample with use formula sampling size. with use technique Stratifeid Random Sampling. Data analysis using Analysis Univariate. Research results: show level knowledge teenager Princess about abortion, obtained as many as 24 respondents (38.1%) have knowledge good, while respondents who know not enough good as many as 39 respondents (61.9%). Whereas level knowledge teenager Princess about health reproduction, obtained as many as 25 respondents (39.7%) have knowledge good, while respondents who know not enough good as many as 38 respondents (60.3%). Conclusion: overview knowledge teenager Princess about abortion and health reproduction at SMA Negeri 2 Kendari districts poasia city vehicle have description knowledge not enough good as many as 39 respondents (61.9%) in knowledge about abortion whereas for knowledge about health reproduction have description knowledge not enough good as many as 38 respondents (60.3%).